2016
DOI: 10.1097/npt.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Therapy on Postural Instability in Parkinson Disease

Abstract: Exercise therapies specifically addressing balance dysfunction are an important treatment option for improving postural stability in persons with PD. Future studies should investigate sustainability of the short-term effects and establish the dose-response relationship of balance training in persons with PD.Video abstract available for additional insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A121).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 55 publications
1
83
2
5
Order By: Relevance
“…According to recommendations [63,64], strength training should be combined with training that includes other components such as balance. This is further underlined by the fact that postural instability contributed independently to perceived walking difficulties in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to recommendations [63,64], strength training should be combined with training that includes other components such as balance. This is further underlined by the fact that postural instability contributed independently to perceived walking difficulties in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, voluntary wheel-running could affect physiological circadian rhythms and delay the phase of peripheral Per2 expression [113]. Also, a metaanalysis showed that physical exercises including Argentine Tango and Tai Ji Quan may be appropriate choices for postural instability therapy in PD [114][115][116]. However, few exploratory studies have examined the effect of physical exercise on circadian systems in PD patients.…”
Section: Circadian Therapymentioning
confidence: 99%
“…Pharmacological research suggests that poor balance in this population is due to malfunctioning afferent sensory integration and decreased 5,6 efferent neuromuscular signals in the central nervous system (CNS). However there is also evidence that balance can worsen with these pharmacological interventions, suggesting 2,7 there are other contributors to fall risk in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is an important neurotransmitter for multiple body functions including movement proficiency. Due to the lack of dopamine, people with PD commonly present with four primary motor symptoms: resting 2,3 tremors, bradykinesia, rigidity, and postural instability. While extensive research is aimed at treating tremors, bradykinesia, and rigidity, little research has analyzed the relationship between posture and stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation